Behavioral Neuroadaptation to Alcohol: From Glucocorticoids to Histone Acetylation - Mons, Nicole; Beracochea, Daniel (Frontiers in Psychiatry, 2016)
A prime mechanism that contributes to the development and maintenance of alcoholism is the dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis activity and the release of glucocorticoids (cortisol in humans and primates, corticosterone in rodents) from the adrenal glands. In the brain, sustained, local elevation of glucocorticoid concentration even long after cessation of chronic alcohol consumption compromises functional integrity of a circuit including the prefrontal cortex, the hippocampus and the amygdala. These structures are implicated in learning and memory processes as well as in orchestrating neuroadaptive responses to stress and anxiety responses. Thus, potentiation of anxiety-related neuroadaptation by alcohol is characterized by an abnormally amygdala hyperactivity coupled with a hypofunction of the prefrontal cortex and the hippocampus. This review describes research on molecular and epigenetic mechanisms by which alcohol causes distinct region-specific adaptive changes in gene expression patterns and ultimately, leads to a variety of cognitive and behavioral impairments on prefrontal- and hippocampal-based tasks. Alcohol-induced neuroadaptations involve the dysregulation of numerous signaling cascades, leading to long-term changes in transcriptional profiles of genes, through the actions of transcription factors such as CREB (cAMP response element binding protein) and chromatin remodeling due to post-translational modifications of histone proteins. We describe the role of prefrontal-hippocampus-amygdala circuit in mediating the effects of acute and chronic alcohol on learning and memory, and region-specific molecular and epigenetic mechanisms involved in this process. This review first discusses the importance of brain region-specific dysregulation of glucocorticoid concentration in the development of alcohol dependence and describes on how persistently increased glucocorticoid levels in prefrontal cortex may be involved in mediating working memory impairments and neuroadaptive changes during withdrawal from chronic alcohol intake. It then highlights the role of cAMP-PKA-CREB signaling cascade and histone acetylation within the prefrontal cortex and limbic structures in alcohol-induced anxiety and behavioral impairments, and how an understanding of functional alterations of these pathways might lead to better treatments for neuropsychiatric disorders.